In situ estimation of actual évapotranspiration. A case study in Argos plain - Giannoulopoulos, P.; Poulovassilis, A. (Bulletin of the Geological Society of Greece, 2007)
The following work refers to an experimental methodology employed for in situ monitoring of specific soil water fluxes constituting water balance components. The test area is located in the plain of Argos - Greece, within an orange grove. A micrometeorological station was installed in the site, equipped with several sensors for real time monitoring of various atmospheric parameters as well as water content and temperature in the soil profile. The soil profile was made accessible for sampling through a rectangular pit which was excavated close to the station. The soil water content was monitored making use ofTDR sensors which were calibrated against the traditional neutron probe technique and also by soil sampling. Tensiometeres were also installed in four different depths for monitoring the matrix potential. A software programme was developed for the analysis and the evaluation of the data collected in a 10 - minute time step. The analysis of the data showed that the three - year average of Actual Evapotranspiration, in this irrigated field, was approximately 857 mm, out of which almost 600mm occur between April and September and 260 mm in the winter period. Those results show that there is no significant water surplus for deep infiltration and aquifer recharge in clayey and clay - loam soils in this region.